2013
DOI: 10.1002/wsb.351
|View full text |Cite
|
Sign up to set email alerts
|

Northern bobwhite response to habitat restoration in eastern oklahoma

Abstract: In response to the decline of northern bobwhite (Colinus virginianus; hereafter, bobwhite) in eastern Oklahoma, USA, a cost-share incentive program for private landowners was initiated to restore early successional habitat. Our objectives were to determine whether the program had an effect on bobwhite occupancy in the restoration areas and evaluate how local-and landscape-level habitat characteristics affect occupancy in both restoration and control areas. We surveyed 14 sample units that received treatment be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Crosby et al (2015) reported that bobwhite presence was a positive predictor of presence for several other species; however, that study did not seek to explain how broad-scale landscape characteristics may influence bobwhite occupancy and co-occurrence with other species. Understanding broad-scale landscape characteristics is also necessary to develop generalizable results that can be applied across different landscapes and to determine appropriate sites for finer-scale management (Crosby et al 2013, Shahan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Crosby et al (2015) reported that bobwhite presence was a positive predictor of presence for several other species; however, that study did not seek to explain how broad-scale landscape characteristics may influence bobwhite occupancy and co-occurrence with other species. Understanding broad-scale landscape characteristics is also necessary to develop generalizable results that can be applied across different landscapes and to determine appropriate sites for finer-scale management (Crosby et al 2013, Shahan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of declining populations of bobwhites have concluded that there is a need to increase the quantity of breeding habitat for quail, though whether or how far breeding habitat should be increased beyond the scope of ranch-level management is unclear (Collins et al 2009). Crosby et al (2013) demonstrated the unsuitability of pasture-scale management via habitat restoration through the Quail Habitat Restoration Initiative. The study examined 29 areas over a period of 3 years to determine whether habitat restoration projects by the initiative had a positive impact on bobwhite abundance.…”
Section: Habitat and Spacementioning
confidence: 99%
“…The study examined 29 areas over a period of 3 years to determine whether habitat restoration projects by the initiative had a positive impact on bobwhite abundance. The study concluded that no positive impact could be observed and postulated that this lack of impact could be explained by the fact that bobwhite population ecology operates on multiple scales, and that pasture-scale management and study would not necessarily take all scales or associated processes into consideration (Crosby et al 2013). Furthermore, Williams et al (2003a) showed that density-dependent abundance in bobwhites varies within their geographical range; variation was highest in the periphery of their range and the authors postulated that this was likely due to environmental factors affecting habitat quality.…”
Section: Habitat and Spacementioning
confidence: 99%
“…Williams et al (2004) suggested that this is because our current habitat management practices are implemented at the wrong spatial scale. Most bobwhite research on habitat to date has been done on a local (,25km 2 ) scale (Kabat and Thompson 1963, Burger and Linduska 1967, Wiseman and Lewis 1981, Taylor et al 1999a, Fies et al 2002, Oakley et al 2002, Riddle et al 2008, Crosby et al 2013) whereas harvest management is usually on a statewide scale (Williams et al 2004). There is a need to transition from both local and statewide practices to more regional management (Peterson et al 2002, Dimmick et al 2002, Williams et al 2004).…”
mentioning
confidence: 99%